You Are Here: UNESCO’s Higher Education Roadmap - Maldonado-Maldonado, Alma (International Higher Education, 2022)
This article analyzes the UNESCO decision on to presenting a Roadmap document at the end of the Third UNESCO World Higher Education Conference instead of a declaration. It problematizes its content and also highlights the aspects that are missing, which are mainly the actions that could be driven by states, governments and societies. On one side the Roadmap could be seen as a sign of openness but on the other a mark of weakness.